Leader Member Exchange Mediates the Relationship between Political Skills and Narcissistic Leadership with Organizational Citizen Behavior - Utomo, Kabul Wahyu; Siahaan, Anggia Boantua (LP3M Universitas Putra Bangsa, 2023)
This test aims to look at the Relationship between Political Skills and Narcissistic Leadership with Organizational Citizen Behavior mediated by Leader-Member Exchange. This study uses Organizational Citizen Behavior as a dependent variable and Political Skills and Narcissistic Leadership as independent variables.This study used quantitative research methods with sampling techniques in the form of purposive sampling which were distributed to office workers in the Central Jakarta area with an age range in the Millennial generation, namely 20 years to 40 years. The number of populations in this study is unknown, so the sampling used the Lemeshow technique with a total sample of 100 respondents. The results of the linear regression in this study show that the proposed hypothesis exists that is appropriate and not with the research carried out. Where the results showed that there was a significant relationship between political skills and OCB but narcissistic leadership with OCB did not have a significant relationship. The results also showed that leader-member exchanges can mediate the relationship between variables of political skills and narcissistic leadership with employee organizational citizen behavior.